PEMBELAAN HAK MANGSA KEMALANGAN JALAN RAYA BERASASKAN INSURANS DAN DIAT: The Defence of Road Traffic Accident Victims’ Rights According to Insurance and Diyah - Samudin, Siti Aisyah; Ismail, Siti Zubaidah (Jurnal Syariah, 2018)
Claims for damages of road traffic accidents in Malaysia are usually made through procedures in court. This occurs when there is a dispute over the liability and quantum of damages that should be paid by the guilty party. In the absence of a dispute, an out-of-court settlement may be exercised. The court process however, should not necessarily be done in Islamic compensation system called diyah. Diyah allows both parties to settle down their claim of damages with the presence of ‘aqilah. If the accused has committed negligence that causes injury or death to the victims, it is obligatory to pay a number of compensation to victim or their heirs. Therefore, the objective of this research is to examine the rights of the victims involved in road traffic accident both through the civil law system and the Islamic compensation system (diyah). An overview of road accident laws in Malaysia has been discussed in this paper including the Civil Law Act 1956 (Act 67), the Road Transport Act 1987 (Act 333), and the Insurance Act 1996 (Act 533). Rights and responsibilities arising from accidents also have been discussed. Using bibliographical studies, observation and semi structured interview as a methods of collecting data, the research finding indicates that victims are not being under a proper defence of their right. The victims have to go through the long process in order to get the quantum awarded by the court or insurance company. Hence, this research proposed compensation system based on diyah. Legal reform is necessary to address this issue.